Commercializing Social Media? How Showrooms on Social Media Fan Pages Influence Customer Behavior - Jung, Jaehwuen; Wang, Shuting (Ada); Wattal, Sunil (MIS Quarterly, 2024)
While marketing on social media fan pages has received widespread research attention, few studies have investigated the impact of adding a showroom to a social media fan page. Showrooms on social media fan pages are unique in that they can amplify the conflicts between businesses’ commercial purposes (selling) and customers’ expectations (socializing) on social media, making it unclear how they might influence customer behavior. In this study, we open this black box by using data from a leading fashion retailer. We found that adding a showroom to a fan page has both positive implications, in that it leads to more user engagement and purchases, and negative implications, in that it leads users to “unfollow” the retailer’s social media fan page. We further found that such impact is moderated by customer willingness to disclose private information. Specifically, the positive (negative) implication is significantly greater (smaller) for customers who are willing to disclose their private information to the retailer on social media. Mechanism-level analyses suggest that adding a showroom to a fan page can increase customer purchases both directly and indirectly by facilitating their engagement with the fan page and that customer willingness to disclose private information negatively moderates the mediation effect of user engagement on purchase behavior. In addition, results from an online experiment indicate that such showrooms can increase unfollowing by undermining users’ social perception of the fan page and raising users’ privacy concerns. Our findings suggest that even when firms see a significant increase in user purchase and activities after adding a showroom on their fan pages, they should carefully consider the potential risk of driving away customers and strategically target users who are less privacy sensitive.